Potential Impact of the ‘Lying Flat’ Phenomenon on Labor Supply and Economic Growth in China - Zhiming Wang; Qingjie Sun (Law and Economy, 2025)
The ‘lying flat’ (躺平) phenomenon has emerged as a significant social and economic trend in China, reflecting a shift in generational attitudes toward work, career ambition, and financial stability. In response to rising living costs, intense work pressures, stagnant wages, and diminishing social mobility, many young Chinese workers are opting out of high-intensity employment, rejecting traditional career aspirations, and embracing minimalist lifestyles. This paper examines the causes and consequences of ‘lying flat,’ analyzing its impact on labor market participation, economic growth, social mobility, and workforce sustainability. The findings suggest that ‘lying flat’ contributes to declining workforce productivity, lower consumer spending, and structural labor market inefficiencies, particularly in high-stress industries such as technology, finance, and manufacturing. Additionally, the movement deepens class divides, as those who disengage from traditional career paths face long-term income stagnation, while those who remain in high-paying jobs continue to accumulate wealth. In response, corporate and government initiatives—such as workplace reforms, employment policies, and financial incentives—have sought to re-engage young workers, but skepticism remains about the effectiveness and sustainability of these measures. The paper also explores global comparisons, including the Great Resignation in the U.S., Quiet Quitting in Western economies, and Hikikomori in Japan and South Korea, to identify potential strategies for addressing labor disengagement. While China’s economic and policy structure differs from other nations, lessons from international labor trends highlight the need for meaningful workplace reforms, economic restructuring, and flexible career pathways to balance workforce participation with evolving worker expectations. Ultimately, the long-term implications of ‘lying flat’ depend on how China adapts its labor policies and corporate strategies to address shifting workforce dynamics. If businesses and policymakers fail to improve labor conditions and economic mobility, the continued disengagement of young workers could weaken China’s economic growth, reduce innovation, and create long-term instability in labor markets. However, if reforms succeed, ‘lying flat’ may serve as a catalyst for rethinking work-life balance, labor protections, and economic sustainability in China’s future workforce.